The Risk Factors for Perioperative Serum Albumin Variation in Pediatric Patients Undergoing Major Gastroenterology Surgery - Liu, Qingshuang; Gao, Kai; Zheng, Chao; Guo, Chunbao (Frontiers in Surgery, 2021)
Background: Albumin is considered a negative acute-phase protein because its concentration decreases during injury and sepsis. The decrease in serum albumin may be important for perioperative morbidity. This study intend to determine the perioperative factors associated with the reduction in serum albumin within 2 postoperative days compared with the preoperative level (∆ALB) and its influence on perioperative outcome in a pediatric general surgical cohort. Methods: This single-center retrospective review included 939 patients who underwent Roux-en-Y hepaticojejunostomy between August 2010 and August 2019. Based on the mean value of ∆ALB (14.6%), patients were separated into two groups, a high ∆ALB group (≥14.6%) and a low ∆ALB group (<14.6%). Multivariable logistic regression analyses were performed to determine the independent risk factors for a reduction in serum albumin. Propensity score matching was performed to adjust for any potential selection bias for the two groups. In 366 matched patients, the influences of operating time on perioperative outcomes, including postoperative recovery, complications measurement, and length of hospital stay between the two groups were analyzed. Results: Among the 996 patients reviewed, 939 patient records were enrolled in the final analysis. Controlling for other factors, multivariable analysis showed that a high CRP on POD 3 or 4 (odds ratio [OR] =2.36 [95% CI, 1.51-3.86]; p =0.007), the presence of Charcot's triad (OR=1.73 [95% CI, 1.05-2.83]; p = 0.031), and a longer operating time (OR=1.18 [95% CI, 1.00 -1.53]; p=0.014) were factors that predicted a high ∆ALB level. A high ∆ALB level was associated with postoperative gastrointestinal functional recovery, reflected by the first defecation (p= 0.013) and first bowel movement (p=0.019) and the high occurrence of postoperative complications (16.1% vs 10.9%, OR, 1.57; 95% CI, 1.02-2.41, P=0.0026). The mean length of postoperative stay of patients in the high ∆ALB group was longer, although no statistically significant difference was observed (p=0.057). Conclusions: We showed that a change in albumin level was associated with postoperative outcome. The risk factors for ∆ALB could be addressed in the perioperative period to permit patients to obtain a safe recovery and discharge after a major abdominal operation.